AYURVEDIC MANAGEMENT OF SUPEROTEMPORAL BRANCH RETINAL VEIN OCCLUSION- A SINGLE CASE STUDY (International Journal of Ayurveda and Pharma Research, 2021)
Branch Retinal Vein Occlusion (BRVO) is the second most frequent retinal vascular disorder. Hypertension and diabetes mellitus are common predisposing factors, which typically lead to atherosclerosis. Superotemporal Branch Retinal Vein Occlusion (STBRVO) is a major type of BRVO. In which retinal oedema and haemorrhages are limited to the area drained by the affected vein. Anti-VEGF injection is the treatment currently provided for the above said condition but it has high recurrent rate and expensive, thus Ayurvedic treatment will help in preventing further visual loss and improvement in visual acuity. Materials and methods: A patient of age 48 approached our OPD complaining of decreased and blurred vision especially at the lower part of visual field of right eye. He had developed the symptoms before 2 month and visited an ophthalmologist; he was diagnosed of STBRVO and took inj. Avastin, but didn’t have any satisfaction, thus he approached our OPD. He was under Ayurvedic treatment for 3 months. Results: There was improvement in visual field and acuity, reduction of macular oedema was found in OCT. Discussion: Here the condition occurred due to the Sanga (obstruction) in Raktha vaha srothas due to Kapha and leads to Vimarga gamana (reversed flow) of Vata, thus Srotho sanga hara treatment by reducing Kapha and making the flow of Vata in correct direction was adopted.